Terapi Kombinasi Montelukast dan Desloratadin pada Pasien Urtikaria Akut yang Tidak Responsif dengan Antihistamin dan Kortikosteroid - Regina, Regina; Wijaya, Lorettha; Stella, Maureen Miracle (Bahasa Indonesia, 2025)
Introduction: Urticaria is a common skin disease, characterized by localized edema that appears suddenly and disappears within 24 hours. Antihitamin-H1 is the drug of choice for urticaria which is sometimes combined with systemic corticosteroids. The use of montelukast in cases of urticaria is still rarely reported. Case Report: A 21-year-old woman came with complaint of itchy bumps all over her body with a dominant burning sensation since 5 days ago. Complaint remained unchanged even after administering up to four doses of desloratadine and a combination of 16 mg methylprednisolone. The complaint finally improved after the patient was given montelukast 10 mg per day combined with desloratadine 5 mg twice a day. Discussion: Leukotriene is a lipid mediator that can increase vasopermeability and vasodilation in the skin. The improvement in symptoms that occurred after the combination therapy of montelukast and desloratadine proved the involvement of leukotrienes in the pathogenesis of this patient's case of acute urticaria. Conclusion: Combination therapy with montelukast and desloratadine may be useful in some cases of acute urticaria. Further studies with sufficient control may be conducted to determine the effectiveness of montelukast in combination with antihistamines for cases of acute urticaria.